2016
DOI: 10.1039/c5nr08881j
|View full text |Cite
|
Sign up to set email alerts
|

Dual emission in asymmetric “giant” PbS/CdS/CdS core/shell/shell quantum dots

Abstract: Semiconducting nanocrystals optically active in the infrared region of the electromagnetic spectrum enable exciting avenues in fundamental research and novel applications compatible with the infrared transparency windows of biosystems such as chemical and biological optical sensing, including nanoscale thermometry. In this context, quantum dots (QDs) with double color emission may represent ultra-accurate and self-calibrating nanosystems. We present the synthesis of giant core/shell/shell asymmetric QDs having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 55 publications
5
76
0
Order By: Relevance
“…Synthesis of GQDs. Synthesis of PbS@CdS QDs was carried out via a two-step cation exchange reaction, as reported in [26,40], followed by the growth of a thick CdS shell. In particular, the PbS cores were synthesized by using OLA as ligands [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of GQDs. Synthesis of PbS@CdS QDs was carried out via a two-step cation exchange reaction, as reported in [26,40], followed by the growth of a thick CdS shell. In particular, the PbS cores were synthesized by using OLA as ligands [40].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, dual emission-systems do not suffer from environmental interference, overcoming limitations arising from inaccurate detection due to the effect on the photoluminescence of refractive index, surrounding environment, presence of quenching agent [9]. Zhao et al [9,[26][27][28] have reported the fabrication of "giant" PbS@CdS@CdS QDs (GQDs) where the PbS core produces an emission band in the near infrared (NIR) region and the CdS shell in the visible portion of the electromagnetic spectrum. Due to the "giant" CdS shell (from 1.5 nm up to several tens nm), these optically active GQDs exhibit very high photostability towards photobleaching, even under continuous laser excitation, and have been demonstrated to be efficient temperature ratiometric and multiparametric probes [9].…”
mentioning
confidence: 99%
“…As a result of their unique internal structure, featuring a sharp, unalloyed, core/shell interface and a 30 meV potential barrier between the core and the shell valence bands ( Figure a), DiB‐NCs exhibit two‐color red and green emission, respectively, from core and shell excitons under low intensity optical excitation (Figure S2, Supporting Information) or electrical pumping . Two‐color light as a result of radiative recombination of excitons localized in different compositional domains of the same heterostructure has been observed also in elongated dot‐in‐rod structures, tetrapods, and spherical core/shell systems …”
Section: Introductionmentioning
confidence: 99%
“…However, the variations and degradation of the surface caused by the processing and aging make this dual emissions be uncontrollable . (ii) By growing thick shells and finely controlling the composition and the crystal structures of core/shell interface in “giant” QDs systems to obtain two types of direct radiative exciton emissions . For example, Zhao et al reported that a novel PbS/CdS “giant” QD system with dual emissions could be used as an ultrasensitive and self‐calibrating thermometer .…”
Section: Introductionmentioning
confidence: 99%